Multivariate analysis: an example of the use of a log-linear model - Souza, José Maria Pacheco de; Benicio, Maria Helena D'Aquino (Revista de Saúde Pública, 1985)
A multivariate analysis of categorical data using a log-linear model for a 2 x 2 x 2 contingency table is presented.